Development Of Evaluation Media Spinning Question For Reading Skills For Seventh G raders At MTsN 2 Padang - Dayana Fadillah (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The teacher uses the old evaluation Media, in the digital age learning evaluation cannot be separated from the impact of technological development, as one of the modern evaluation Media is Spinning Question.  This research is a development research with 4D model which consists of four steps, namely; definition, design, development, and deployment. However, the researcher limits the development procedure in terms of assessing media based on experts in terms of media and languages. The development procedure in this research is; the development needs analysis stage, namely the analysis 2013 Curriculum,  student book, the form of questions used and analysis  of the needs of Arabic teachers and students. The results of the data obtained show a rating of "Excellent" in the sense that the development of this media is very much needed. Then the planning stage; starting from writing a grid of questions, writing question and making evaluation media on Spinning Question. After you have finished making your Spinning Question evaluation media product, proceed to the development stage, namely; with expert verification, product modification and final production. The media validation results show a "Very Good" rating, which means that Spinning Question can be used in evaluation reading skills for seventh graders in Islamic Junior High School two Padang